Stella safeguards the oocyte methylome by preventing de novo methylation mediated by DNMT1. (6th December 2018) - Li, Yingfeng; Zhang, Zhuqiang; Chen, Jiayu; Liu, Wenqiang; Lai, Weiyi; Liu, Baodong; Li, Xiang; Liu, Liping; Xu, Shaohua; Dong, Qiang; Wang, Mingzhu; Duan, Xiaoya; et al.
Abstract Postnatal growth of mammalian oocytes is accompanied by a progressive gain of DNA methylation, which is predominantly mediated by DNMT3A, a de novo DNA methyltransferase1, 2 . Unlike the genome of sperm and most somatic cells, the oocyte genome is hypomethylated in transcriptionally inert regions2–4 . However, how such a unique feature of the oocyte methylome is determined and its contribution to the developmental competence of the early embryo remains largely unknown. Here we demonstrate the importance of Stella, a factor essential for female fertility5–7, in shaping the oocyte methylome in mice. Oocytes that lack Stella acquire excessive DNA methylation at the genome-wide level, including in the promoters of inactive genes. Such aberrant hypermethylation is partially inherited by two-cell-stage embryos and impairs zygotic genome activation. Mechanistically, the loss of Stella leads to ectopic nuclear accumulation of the DNA methylation regulator UHRF18, 9, which results in the mislocalization of maintenance DNA methyltransferase DNMT1 in the nucleus. Genetic analysis confirmed the primary role of UHRF1 and DNMT1 in generating the aberrant DNA methylome in Stella-deficient oocytes. Stella therefore safeguards the unique oocyte epigenome by preventing aberrant de novo DNA methylation mediated by DNMT1 and UHRF1. Stella, a factor essential for female fertility, protects the oocyte methylome in mice by suppressing de novo DNA methylation mediated by the DNA methyltransferase DNMT1.